Law Enforcement Opens Medical Records through Public Relations Media of Langsa Hospital - Tariadi Tariadi; Radhali Radhali; H.S Brahmana; Eko Hadiyanto (SOEPRA, 2020)
Abstract: Medical record is a file that contains records and documents about the patient's identity, examination, treatment, actions, and other services that have been provided to patients. This study aims to determine the legal arrangements regarding the medical record, to find out law enforcement against the Public Relations of Langsa Public Hospital publish patient medical records in online media and to find out the obstacles and efforts made in law enforcement against the Public Relations of Langsa Public Hospital that open patient medical records. The method used in this study is normative and empirical juridical. 1) In medicine, it is not permissible for a doctor or employee of a public hospital to open a medical record through the Public Relations media of Langsa Regional Hospital according to Law Number 29 of 2004 Article 51. 2) Law enforcement against someone who opens a medical record at Langsa Regional Hospital is considered ineffective because law enforcement officials, in this case, are not serious in handling cases that should be prosecuted. 3) Obstacles in law enforcement in Langsa Regional Hospital, namely that there are still overlapping laws by the police so that law enforcement cannot be carried out fairly and the efforts made in law enforcement against Langsa Regional Hospital that open medical records by means of supervision and coordination between leadership and staff in hospitals Langsa.Keywords: Law Enforcement, Medical Records, Media Abstrak: Rekam medis merupakan berkas yang berisi catatan dan dokumen tentang identitas pasien, pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien. Penelitian ini bertujuan untuk mengetahui pengaturan hukum tentang rekam medis, untuk mengetahui penegakan hukum terhadap pihak Humas RSUD Langsa mempublikasikan rekam medis pasien di media online dan untuk mengetahui hambatan dan upaya yang dilakukan dalam penegakan hukum terhadap pihak Humas RSUD Langsa yang membuka rekam medis pasien. Metode yang digunakan penelitian ini adalah yuridis normatif dan empiris. 1) Dalam medis, tidak di bolehkan bagi seorang dokter maupun pegawai rumah sakit umum untuk membuka rekam medis melalui media Humas RSUD Langsa yang atas Undang-Undang Nomor 29 Tahun 2004 Pasal 51. 2) Penegakan hukum terhadap seseorang yang membuka rekam medis di RSUD Langsa dinilai tidak efektif dikarenakan aparat penegak hukum dalam hal ini tidak serius dalam menangani kasus yang seharusnya dapat di pidanakan. 3) Hambatan dalam penegakan hukum di RSUD Langsa yaitu masih adanya timpang tindih hukum yang dilakukan oleh aparat kepolisian sehingga penegakan hukum tidak dapat dilaksanakan secara adil dan adapun upaya yang dilakukan dalam penegakan hukum terhadap pihak RSUD Langsa yang membuka rekam medis dengan cara adanya pengawasan dan koordinasi antara pimpinan dan staf di RSUD Langsa.Kata Kunci: Penegakan Hukum, Rekam Medis, Media